Landscape archaeology in the Chinese Altai Mountains – Survey of the Heiliutan Basin. (June 2017) - Caspari, G.; Plets, G.; Balz, T.; Fu, B.
Abstract: Due to difficult access, the Southern Chinese Altai has so far been understudied, despite being a key region for understanding cultural transfers and the spread of ideas between East and West during the Eurasian Bronze and Iron Age. The Dzungaria Landscape Project in its first campaigns has set out to document the variety of archaeological monuments in the southern Chinese Altai by means of remote sensing and GPS-based intensive survey. It can be shown that the region experienced a peak in anthropogenic activity during the early and middle Iron Age which culturally ties in with the northern Russian Altai (Pazyryk culture) and later shifts towards strong influences from the Semirechye.